Women’s Dignity in the Qur’an: A Comparative Study of Classical and Modern Tafsir - Kaniz Fatima Busra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The Qur'an established women as socially and spiritually independent people, in contrast to pre-Islamic societies that saw them as legal servants. However, its inherent dignity has frequently been overshadowed by cultural additions. In order to recover the genuine Qur'anic framework for historical rights and female empowerment, this study compares classical and current exegesis. A qualitative and comparative hermeneutical method is used in the study. It compares contemporary interpretations found in Tafsir Al-Misbah and Tafsir Al-Maraghi with classical sources like Tafsir al-Tabari and Tafsir Ibn Kathir. It also documents the actual use of female authority in Islamic history by incorporating historical-empirical data from biographical narratives such as Al-Bidayah wa'l-Nihayah. According to the research, contemporary interpretations emphasise